2021
DOI: 10.1186/s13014-020-01741-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of pathological good response in locally advanced rectal cancer

Abstract: Purpose The aim of this study was to identify the clinical predictors of pathological good response (PGR) after neoadjuvant chemoradiotherapy (nCRT) in locally advanced rectal cancer (LARC) to clarify the indications for local excision. Methods and materials A total of 173 patients with LARC (cT3–4/N +) who were treated with nCRT followed by surgery were enrolled in our retrospective study. Patients were categorized into two groups according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…In a retrospective study comprising 173 LARC patients, a DTAV <5 cm was significantly associated with favorable pathological response (defined as ypT0-1N0). 66 Similarly, a positive correlation of DTAV <3 cm with complete response was reported by other investigators. 57 However, these findings could not be confirmed by other studies, 59 , 67 and even opposite results were described.…”
Section: Introductionsupporting
confidence: 66%
“…In a retrospective study comprising 173 LARC patients, a DTAV <5 cm was significantly associated with favorable pathological response (defined as ypT0-1N0). 66 Similarly, a positive correlation of DTAV <3 cm with complete response was reported by other investigators. 57 However, these findings could not be confirmed by other studies, 59 , 67 and even opposite results were described.…”
Section: Introductionsupporting
confidence: 66%
“…Three tumor size-related variables based on MRI (pretreatment MTL, posttreatment MTL, and posttreatment MTT) showed significant differences between patients with pGR and non-pGR in the univariable analysis; however, all of them lost predictive potential after multivariable analysis for the multiscale model. In addition, some studies have reported that pretreatment and posttreatment carcinoembryonic antigen levels were associated with pGR, 17,40 but the current study found no differences. The ability of tumor size-related variables and carcinoembryonic antigen level to predict pGR is controversial and needs to be investigated further.…”
Section: Discussioncontrasting
confidence: 94%
“…The achievement of a complete remission provides the possibility for organ-preserving surgery or a non-operative, watch-and-wait (W&W) approach. Research efforts have been directed toward identification of clinical and other parameters that could help predict pCR after preoperative treatment [ 14 , 15 , 16 , 17 , 18 , 19 ]. However, several unclear issues, particularly related to the importance of clinical T-stage (cT-stage), tumour length, presence of extramural vascular invasion (cEMVI+), mesorectal fascia (cMRF+) involvement, and clinical laboratory values need to be clarified [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%